Wheat flour as carbon source on water quality, growth performance, hemolymph biochemical and immune parameters of Pacific white shrimp (Penaeus vannamei) juveniles in biofloc technology (BFT) - Mohammad Hossein Khanjani; Jamshid Eslami; Maurício Gustavo Coelho Emerenciano (Aquaculture Reports)
This study examined how adding wheat flour (relative to daily feed) affected water quality, growth performance, body composition, hemolymph biochemical and immunity activities of Penaeus vannamei. In 5 experimental enclosures, pacific white shrimp juveniles weighing an average of 2.80 g were reared for 49 days at a density of 1 g/L. The experimental groups include a control group (without wheat flour, 35–50 %/day water exchange) and four biofloc treatments containing wheat flour in proportions of 25 % (WF25), 50 % (WF50), 75 % (WF75) and 100 % (WF100) of daily feed added in the water. The method of feeding and the type of feed was the same in all treatments. In the control group, the highest amounts of total ammonium nitrogen (TAN) (1.14 mg/L), nitrite (8.15 mg/L), and nitrate (3.60 mg/L) were observed (P < 0.05). In biofloc WF50 and WF75 treatments, the highest body weight (9.09–9.18 g), feed efficiency (74.11–74.68 %) and survival rate (93.20–93.83 %) were obtained (P < 0.05). Adding wheat flour to the rearing system improved the biochemical composition of shrimp bodies, so that the control group had the lowest level of protein (75.31 % DW), lipid (6.81 % DW), and ash (11.48 % DW) (P < 0.05). With wheat flour added to the rearing system, shrimp hemolymph glucose and triglyceride levels increased, and the highest levels of glucose were obtained in treatments WF50 (41.33 mg/dL) and WF75 (42.0 mg/dL). Adding wheat flour to the rearing system increased shrimp hemolymph immune activity. The control group exhibited the lowest levels of lysozyme (19 u/mL/min) and phenoloxidase (0.41 u/mL). The results demonstrated that by adding wheat flour to the biofloc cultivation system (under the conditions of this study) in the amount of 50–75 % of the daily feed ration, the water quality, growth performance, feed efficiency, survival rate, hemolymph biochemical, and immunity activities of P. vannamei improved.